2017
DOI: 10.1016/j.sjpain.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A novel miniature, wireless neurostimulator in the management of chronic craniofacial pain: Preliminary results from a prospective pilot study

Abstract: AbstractObjectiveTo report a novel wireless neuromodulation system for treatment of refractory craniofacial pain.BackgroundPrevious studies utilizing peripheral nerve stimulation (PNS) of the occipital and trigeminal nerves reported positive outcomes for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…In clinical scenario, successful wireless stimulation and significant pain relief was observed in patients with back pain, leg pain, neuralgia following herpes zoster, craniofacial pain, occipital neuralgia, and complex regional pain syndrome [17][18][19][20]. Adverse events or complications in these short case series and reports were minimal.…”
Section: Discussionmentioning
confidence: 81%
“…In clinical scenario, successful wireless stimulation and significant pain relief was observed in patients with back pain, leg pain, neuralgia following herpes zoster, craniofacial pain, occipital neuralgia, and complex regional pain syndrome [17][18][19][20]. Adverse events or complications in these short case series and reports were minimal.…”
Section: Discussionmentioning
confidence: 81%
“…Outcome was measured simply in terms of whether or not patients were satisfied with the results; on this basis, 90% of implanted cases were successful at 1 year, although by three years this had fallen to 51%. Weiner et al reported on ten patients implanted with a novel wirelessly powered percutaneous device, who obtained a mean 82% pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Where all these measures are ineffective, or where medication causes intolerable side-effects, neuromodulation may be an option. Stimulation has been applied at a range of sites, including peripherally using subcutaneous electrodes in the face (2)(3)(4)(5)(6)(7)(8)(9), at the Gasserian ganglion (10)(11)(12), and centrally with high cervical spinal cord stimulation (targeting the spinal trigeminal nucleus) (13)(14)(15), deep brain stimulation (16) (targeting the ventroposteromedial nucleus of the thalamus and/or the periaqueductal gray matter), or motor cortex stimulation (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The dipole antenna of the wireless system (at 915 MHz) could energize the stimulators implanted at a depth of 12 cm in porcine models, especially efficient with a 4.3 cm antenna. Successful stimulation has been observed to provide significant pain relief in patients with back and leg pain with FBSS [19,20], post herpetic neuralgia [21], refractory craniofacial pain [22], occipital neuralgia [23], and CRPS [24]. Patients undergo implantation of the INS with integrated microcircuits enabling coupling with a pulse generator, while the wireless pulse generator circuit excludes surgical implantation of the IPG, thus eliminating complications related to multiple surgical incisions and interventions for failed IPG or its extension cables.…”
Section: Discussionmentioning
confidence: 99%
“…Information in the chapter includes material from the patent applications. Author has copyrights on the publications referenced [18,19,22,23].…”
mentioning
confidence: 99%